2002
DOI: 10.1029/2001gl014443
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of scattering of tropospheric radiation by PSCs in mid‐IR limb emission spectra: MIPAS‐B observations and KOPRA simulations

Abstract: Polar stratospheric clouds (PSCs) were observed by the high resolution mid infrared Michelson Interferometer for Passive Atmospheric Sounding, Balloon borne version (MIPAS‐B), on a flight from Kiruna/Sweden on January 11, 2001. Highly resolved spectral features in the limb measurements could only be explained by tropospheric radiation scattered into the line of sight by large PSC particles. Furthermore, model calculations showed that for PSCs with particles of radius ≥1 μm, a significant part of the broadband … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
93
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(97 citation statements)
references
References 23 publications
3
93
0
Order By: Relevance
“…The forward modeling accounted for Mie scattering through a calculation of extinction coefficient for the PSC particles but did not explicitly include terrestrial or solar scattering into the line of sight of the instrument. However at 820 cm À1 , these effects, as reported by Höpfner et al [2002], do not show any ability to produce distinct infra-red bands such as the one observed in this study.…”
Section: à3mentioning
confidence: 43%
See 1 more Smart Citation
“…The forward modeling accounted for Mie scattering through a calculation of extinction coefficient for the PSC particles but did not explicitly include terrestrial or solar scattering into the line of sight of the instrument. However at 820 cm À1 , these effects, as reported by Höpfner et al [2002], do not show any ability to produce distinct infra-red bands such as the one observed in this study.…”
Section: à3mentioning
confidence: 43%
“…In particular, observations of Arctic PSCs obtained with a balloon-borne instrument (MIPAS-B2) coupled with simulations of the observed spectra have shown that large PSC particles (>1 mm mean radius) could scatter significant fractions of upwelling tropospheric radiation into limb views [Höpfner et al, 2002]. Höpfner et al also reported a sharp step observed between 815 and 825 cm À1 and attributed the change in gradient to the n 2 band of the NO 3 À ion in nitric acid containing PSC particles.…”
Section: Introductionmentioning
confidence: 99%
“…There is also a small but strong feature at this wave number range (Fig. 2), caused by the ν 2 band emissions of NO − 3 (Höpfner et al, 2002). In previous laboratory measurements of NAT refractive indices, the feature was not pronounced enough to reproduce the atmospheric infrared limb observations of the signature; but in a reanalysis of the Biermann et al (2000) NAT film measurements in conjunction with radiative transfer model calculation, Höpfner et al (2006a) showed the unambiguous assignment that NAT particles with r < 3 µm produce the spectral signature in the measured spectra.…”
Section: Two-colour Ratio Methodsmentioning
confidence: 90%
“…The retrieval model used is the KOPRA-KOPRAFIT (Karlsruhe Optimized and Precise Radiative transfer Algorithm) suite, allowing us to directly retrieve aerosol parameters from observed radiances by coupling a Mie model with the line-by-line radiative transfer scheme Höpfner et al, 2002Höpfner et al, , 2006. For aerosol composition we assume a 75 % by weight (75 wt %) H 2 SO 4 -H 2 O solution, as the stratospheric sulfuric aerosol composition typically varies between around 70 and 80 %, as obtained by equilibrium calculations (Carslaw et al, 1995) and observations (e.g.…”
Section: Chemical Transport Modelmentioning
confidence: 99%